Sistem Pengendalian Internal Pada Lembaga Amil Zakat (Studi Komparatif Lembaga Amil Zakat Al Azhar Peduli Ummat dan Lembaga Amil Zakat Dompet Dhuafa) - Amalia Ika Paristu (Jurnal Dinamika Akuntansi dan Bisnis, 2014)
This research analyzed the application elements of the internal control amil zakat institutions. Sample selection methods was judgement sampling while the data analysis method used is descriptive qualitative analysis and comparison. These results indicate that Dompet Dhuafa Amil Zakat Institutions better implement elements of internal control includes the control environment, risk assessment, control activities, information and communication and monitoring.. The research alaso indicated that the internal monitoring Dompet Dhuafa Amil Zakat Institutions requires sufficient human resources and adequate internal control would be held in the specific time.ThThis research analyzed the application elements of the internal control amil zakat institutions. Sample selection methods was judgement sampling while the data analysis method used is descriptive qualitative analysis and comparison. These results indicate that Dompet Dhuafa Amil Zakat Institutions better implement elements of internal control includes the control environment, risk assessment, control activities, information and communication and monitoring.. The research alaso indicated that the internal monitoring Dompet Dhuafa Amil Zakat Institutions requires sufficient human resources and adequate internal control would be held in the specific time.